Neutral Zone: Concept and Technique Application for Managing Severely Resorbed Mandibular Ridges – A Case Report - Nuriyanto, Ainy F.; Rostiny, Rostiny; Agustono, Bambang (Universitas Sam Ratulangi, 2022)
Abstract: Full dental prosthesis rehabilitation on flat mandibular ridge has been a difficult case for clinicians for a long time. A huge resorption of mandibular ridge results in inadequate retention, and tounge muscle pressure, as well as lip and cheek muscles, causing a decrease in denture’s stability and retention. Neutral zone is a potential area or position where lips and cheek on one side, and tounge on the other side have balance pressure. We reported a 60-year-old male patient with chief complaints of difficulty in mastication, and loose upper and lower dentures. He also complained of denture moving during swallowing and speaking. In case management, the aim was to acquire optimum stability of the denture and arrangement of the mandibular teeth in full dental prosthesis guided by using the neutral zone. Preliminary impression was done by using alginate, then, horizontal and vertical jaw relation was recorded by using bite rim. Suction method impression technique was used to acquire functional impression. Lower denture teeth arrangement adapted the result of neutral zone impression. Acrylic denture was being contoured to adjust the natural anatomy of the oral cavity. In conclusion, the patient got a new full denture with maximum retention and stability while speaking as well as masticating. This article discussed about making of full dental prosthesis with pressure point on neutral zone impression technique on flat mandibular ridge caused by huge resorption.Keywords: flat mandibular ridge; denture stability; neutral zone; impression technique